PENGARUH UKURAN DEWAN DIREKSI, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN UKURAN KOMITE AUDIT TERHADAP PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI TAHUN 2009 - 2014 - DWI OKTAVIANI, HAPPY (Jurnal Akuntansi AKUNESA, 2016)
The research purpose to analyze the influence of board director’s size, proportion of independent commissioners, and audit comittee’s size on practice of earnings management is measured by discretionary accrual. Population of this research is all of pharmacy companies listed in Indonesia Stock Exchange period 2009-2014. This research used 7 pharmacy companies, selected using purposive sampling method. Data were analyzed using multiple regression method. Based on the result of research indicate that board director’s size, proportion of independent commissioners, and audit comittee’s size on practice have no influence on practice of earnings management.